Realism and individualism : Charles S. Peirce and the threat of modern nominalism - Oleksy, Mateusz W (Bochumer Studien zur Philosophie, 2015)
Realism and Individualism. Charles S. Peirce and the Threat of Modern Nominalism discusses the main problems, tenets, assumptions, and arguments involved in Charles S. Peirce's early and late realist stances and subjects to critical scrutiny the still dominant view that Pragmatic Realism merely extends or refines new arguments in support of Scholastic Realism without questioning its basic assumptions. The book presents a critical overview of Peirce's views on modern nominalism and offers a novel approach to the social-anthropological underpinnings of his realism, especially Pragmatic Realism vis à vis the individualist tendencies in modern thought.The book is of interest to scholars and students of philosophy, especially students of American pragmatism, anthropology, linguistic pragmatics, as well as to anyone interested in Charles S. Peirce, Duns Scotus, Ockham, and generally to semioticians, social scientists, and sociologists.